2017
DOI: 10.4103/2249-4863.222025
|View full text |Cite
|
Sign up to set email alerts
|

Risk factor of type 2 diabetes mellitus among adolescents from rural area of India

Abstract: Context:Health system is likely to encounter more adolescents with Type 2 diabetes mellitus (T2DM) as a consequence of obesity and sedentary lifestyle. Intervention at various stages of the life cycle is needed as cumulative effect of risk factors accumulated from fetal life to adult increases risk of noncommunicable disease.Aims:The aim of this study was to find out awareness regarding T2DM and distribution of risk factor for T2DM in adolescents from the rural areas of Wardha district, India.Methodology:A cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The mean waist and hip circumference were found to be 95.52 ± 10.07 and 98.58 ± 7.48 cm , respectively. The mean waist-hip ratio was 0.97 ± 0.62, which is very much similar to the study done by Gaidhane et al [ 14 ] as they found it 0.89. The mean SBP and DBP were 128.79 ± 10.69 and 80.29 ± 8.08, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…The mean waist and hip circumference were found to be 95.52 ± 10.07 and 98.58 ± 7.48 cm , respectively. The mean waist-hip ratio was 0.97 ± 0.62, which is very much similar to the study done by Gaidhane et al [ 14 ] as they found it 0.89. The mean SBP and DBP were 128.79 ± 10.69 and 80.29 ± 8.08, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…For optimum subject compliance and convenience, RCBG levels were measured with Glucometer (Dr. Morpen GluoOne Model BG-03), following all aseptic precautions and under instrument recommended guidelines. [8,18,19] RCBG < 140 mg/ dl was considered as normal and ≥140 mg/dl was taken as hyperglycemia to classify subjects. [19] Weight (Wt) and height (Ht) were measured by resident doctors of the department.…”
Section: Methodsmentioning
confidence: 99%
“…[8,18,19] RCBG < 140 mg/ dl was considered as normal and ≥140 mg/dl was taken as hyperglycemia to classify subjects. [19] Weight (Wt) and height (Ht) were measured by resident doctors of the department. Subjects were instructed to remove heavy clothing or ornaments and shoes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The World Health Organization projects that diabetes will be the 7th leading cause of death in 2030 (Mathers et al, 2006). Diabetes is one of the leading causes for renal failure, visual disability, and progressive loss of vision, heart diseases, vascular and neurological disease processes manifested as diabetic foot disease which leads to amputation (Chigurupati et al, 2019;Gaidhane et al, 2017). There is now ample evidence that it is possible to avoid type 2 diabetes (which accounts for over 90% of diabetes worldwide) (Dagogo-Jack, 2017).…”
Section: Introductionmentioning
confidence: 99%